Perubahan Iklim, Degradasi Aset, dan Aksesibilitas Kredit: Peran Penilaian Jaminan dalam Sektor Pegadaian di Indonesia - Bahrul Umam; Villatus Sholikhah (Jurnal Media Ekonomi (JURMEK), 2026)
Abstract Purpose: This study explores how climate-related asset degradation influences collateral appraisal practices and credit accessibility at the Patrang Pawnshop Service Unit (UPC Patrang), East Java, Indonesia. Research Methodology: A qualitative case study approach was applied through in-depth interviews, field observations, and document analysis involving managers, appraisers, customer service officers, and customers. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, supported by source and method triangulation. Results: The findings show that increased humidity, fluctuating weather, and environmental exposure accelerate deterioration of motorcycles and electronic devices used as collateral. Appraisers therefore consider climate-related asset-condition risks, in addition to conventional appraisal criteria, when determining collateral values. These adjustments reduce borrowing capacity for some customers and affect financing access for household consumption and microbusiness activities. Conclusion: Climate-related asset degradation has managerial implications for collateral valuation and credit accessibility. The study develops a mechanism linking climate risk, asset degradation, appraisal adjustment, and credit access in the UPC Patrang context. Limitations: The study is limited to one pawnshop unit and two dominant collateral categories. Contributions: This study contributes to appraisal management, climate risk management, and financial inclusion by proposing climate-sensitive appraisal guidelines, better documentation, and enhanced appraiser capacity and prudent lending practices.